Produção de biomassa e teor de cumarina em folhas de guaco (Mikania laevigata Sch. Bip. ex Baker) em diferentes idades da planta - Santos, Dayane Graziella Pereira de Oliveirs dos [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
The species Mikania laevigata Sch. Bip. ex Baker, popularly known as guaco, belongs to the Asteraceae family and it is native to southern Brazil it is among the medicinal plants adopted by the Unified Health System in Brazil (SUS). M. laevigata is a promising option in agricultural cultivation of medicinal plants and is accessible to small farmers, in view of the growing demand of the Brazilian market for herbal medicines. Since medicinal plants are classified as natural products, the law allows them to be grown and marketed it they achieve the required quality standards. This work was conducted at the Lageado Experimental Farm, Faculty of Agricultural Sciences - UNESP, Botucatu, State of São Paulo. The objective of this research was to evaluate the productivity of biomass and coumarin content of guaco harvested at different ages of the plant. It was observed higher productivity for the variables evaluated at eleven months of guaco, obtaining 0.96 t ha-1 of dry leaf and there was no statistical difference in the coumarin content at 7, 9, and 11 months of age Mikania laevigata. The conditions under which the survey was conducted, the higher biomass yield x coumarin content of guaco was obtained at 11 months of age, which enabled the best result for the extraction yield of coumarin in dry leaves.

A espécie Mikania laevigata Sch. Bip. ex Baker, popularmente conhecida como guaco, pertence à família Asteraceae, é originária da região sul do Brasil e está entre as plantas medicinais adotadas pelo Sistema Único de Saúde do Brasil. M. laevigata é uma opção agrícola promissora no cultivo das medicinais, estando acessível ao pequeno produtor, tendo em vista a crescente demanda do mercado consumidor brasileiro por fitoterápicos. Uma vez que as plantas medicinais são classificadas como produtos naturais, a lei permite que sejam cultivadas e comercializadas desde que se atinja o padrão de qualidade necessário. O presente trabalho foi instalado e conduzido na Fazenda Experimental Lageado, da Faculdade de Ciências Agronômicas - UNESP, Campus de Botucatu, Estado de São Paulo. O objetivo desta pesquisa foi avaliar a produtividade de biomassa e teor de cumarina do guaco colhido em diferentes idades da planta. Foi observada maior produtividade para as variáveis avaliadas aos onze meses de idade do guaco, obtendo 0,96 t ha-1 de matéria seca de folha sendo que não houve diferença estatística quanto ao teor de cumarina aos 7, 9, e 11 meses de idade de Mikania laevigata. Nas condições em que foi realizada a pesquisa, o maior rendimento de biomassa x teor de cumarina foi obtido aos 11 meses de idade do guaco, o qual possibilitou o melhor resultado para o rendimento extrativo de cumarina em folhas secas.
Biomass production and coumarin content in different ages of guaco leaves (Mikania laevigata Sch. Bip. Ex Baker)
Keywords: Medicinal plants; Phytochemistry; Spectrophotomete; Asteraceae; Cultivo de plantas medicinais; Espectrofotômetro; Fitoquímica